Economic analysis of large-scale farm biogas power generation system considering environmental benefits based on LCA: A case study in China. (10th June 2020) - Zhang, Caiqing; Xu, Yilin
Abstract: Biogas power generation systems present significant environmental and social benefits. Various countries have attached great importance to clean energy production, although its direct economic benefits are not significant. Nonetheless, the increasing interest in biogas projects has enhanced the need for accurate economic analysis. In this paper, an economic analysis method combined with LCA is proposed, and the monetary value of environmental benefits are innovatively added to the income of a biogas project. First, LCA-based environmental benefit analysis is carried out. Second, environmental benefits are calculated in monetary terms with a quantitative method. Finally, environmental benefits are added to the project income. Specifically, the external effect is internalized. In addition, economic indicators of the project are calculated and compared, complemented by a sensitivity analysis. A case study of the Jing An biogas power generation project reveals that its environmental impact is lower by 6264.17 person-equivalent standard loads compared with the impact of coal-fired generation of equivalent power. Furthermore, the net present value and the internal rate of return of this project increase to 59.40 million RMB and 19.85%, respectively, after the monetary value of the environmental benefits is incorporated. The results suggest that the proposed analysis method can reflect the economic benefits of biogas power generation projects more accurately and comprehensively than standard economic analyses and is applicable to large-scale farm biogas power generation projects integrating agriculture, livestock, electricity and fertilizer. Graphical abstract: Image 1 Highlights: Economic analysis combined environmental analysis improves the analysis accuracy. Net present value considering environmental benefits increased 483.68 million RMB. Case study proves that the effectiveness of the method. This method could be applied to large-scale farm biogas power generation system.